Westonci.ca offers quick and accurate answers to your questions. Join our community and get the insights you need today. Get immediate and reliable answers to your questions from a community of experienced professionals on our platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
By writing sin 3x = sin(2x+x), the result of the expression sin 3x = 3 sin x - 4 sin^3 x is true as shown in the proof.
Given the trigonometry expression:
sin 3x = sin(2x+x),
In trigonometry identity;
[tex]Sin(A+B) = sinAcosB + cosAsinB[/tex]
The expression above will then become;
[tex]sin(2x+x) =sin2xcosx+cos2xsinx\\sin(2x+x) =2sinxcosxcosx + (1-2sin^2x)sinx\\sin(2x+x) =2sinxcos^2x + (1-2sin^2x)sinx\\[/tex]
Recall that sin^2x + cos^x = 1, hence;
[tex]sin(2x+x) =2sinx(1-sin^2x)+ (1-2sin^2x)sinx\\Expand\\sin(2x+x) =2sinx-2sin^3x+ sinx-2sin^3x\\sin(2x+x) =2sinx + sinx-2sin^3x-2sin^3x\\sisn(2x+x) = 3sinx-4sin^3x[/tex]
This shows that [tex]sin3x =3sinx-4sin^3x[/tex] (Proved!)
Learn more here: https://brainly.com/question/7331447
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.